VD_FINDINFO Jug / 2011 / 53 vom 10. März 2011 - VD Tribunal cantonal (2011)
PARTAGESENS GÉNÉRAL, PRESTATION DE LIBRE PASSAGE, PRÉVOYANCE PROFESSIONNELLE | 22 LFLP, 30c al. 6 LPP, 7 OLP, 8a OLP, 12 OPP2